2010
DOI: 10.1002/qua.22908
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study on the smallest endohedral metallofullerenes: TM@C20 (TM = Ce and Gd)

Abstract: ABSTRACT:The structure, electronic property, and infrared spectroscopy of endohedral metallofullerenes TM@C 20 (TM ¼ Ce and Gd) have been systematically investigated with the aid of the hybrid DFT-B3LYP functional. It is found that in the endohedral metallofullerenes the average CAC bond lengths are obvious longer than those of empty cage. The frontier orbital analyses show that the endohedral metallofullerene Gd@C 20 has the high-thermodynamic stability. Natural population analysis also tells us that only in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…The calculated spectrum for neutral C 20 (figure 2) agrees well with previous literature data (B3LYP with the 6-31++G basis [38] and 6-31G(d) basis [39]), featuring two primary peaks at 1324 cm −1 (7.55 µm) and 769 cm −1 (13.00 µm). Peaks in these two spectral regions are seen in many of the small fullerene spectra discussed below.…”
Section: (B) C 20 the Smallest Cagesupporting
confidence: 87%
“…The calculated spectrum for neutral C 20 (figure 2) agrees well with previous literature data (B3LYP with the 6-31++G basis [38] and 6-31G(d) basis [39]), featuring two primary peaks at 1324 cm −1 (7.55 µm) and 769 cm −1 (13.00 µm). Peaks in these two spectral regions are seen in many of the small fullerene spectra discussed below.…”
Section: (B) C 20 the Smallest Cagesupporting
confidence: 87%
“…25,26 Recently, theoretical predictions of metallofullerenes containing transition metal atoms have indicated that their electronic and optical properties can be properly tuned. 27,28 All these features also deserve to be carefully evaluated in the context of the silicon cage clusters containing transition metal atoms.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of DFT with small-core RECPs has been shown to provide good results for lanthanide and actinide systems at a reasonable computational cost. 47,53,54 To understand the charge reorganization due to the formation of the M@C 20 cluster from M and C 20 species, the partial atomic charges were calculated using the Lo ¨wdin and Hirshfeld schemes as implemented in the Multiwfn program. 64 The Voronoi deformation density (VDD) 65 charges were calculated from the flow of electron density to or from a certain atom or a fragment due to the bond formation, thus evaluating the charge rearrangements due to the formation of the complex between the lanthanide or actinide atom/ ion and C 20 fragments.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Recently, neutral Ce@C 20 and Gd@C 20 clusters and 3d transition metal atom encapsulated C 20 clusters have been studied theoretically. [47][48][49] These clusters have C 2h symmetry, which is much lower than the I h symmetry, probably because of the absence of a magic number electronic configuration. Recently, Manna et al theoretically predicted a new series of M@C 20 34 (M = Pr À , Pa À , Nd, U, Pm + , Np + , Sm 2+ , Pu 2+ , Eu 3+ , Am 3+ , Gd 4+ , and Cm 4+ ) clusters, a 26-electron system with the I h symmetry, and explained their enhanced stability from the aspect of a large HOMO-LUMO energy gap, large binding energy, etc.…”
Section: Introductionmentioning
confidence: 99%